KEHIDUPAN SOSIAL DAN KEAGAMAAN ORANG BUGIS DALAM ENCIPTAKAN HARMONI DI DUSUN PULAU SOPPE DESA BATU PUTIH KECAMATAN POLEANG SELATANKABUPATEN BOMBANA - Syamsuddin, Andi; Sifatu, Wa Ode; Basri, La Ode Ali (Universitas Halu Oleo, 2021)
This research aims at: (1) describing the social and religious life of Bugis people in Creating Harmony at Soppe Island, BatuPutih Village, Poleang Selatan District of Bombana Regency. The theory for reading this research refers to Clifford Geertz's thoughts on Ethos, Worldview and Analysis of Sacred Symbols with qualitative methods. Soppe Island Hamlet is a village inhabited by Bugis people whose community lives always work together, care for each other and help with a deep sense of kinship among them. Community relations are familial in nature, which they refer to a term of situndrung, which means one trip is implemented in social, economic, religious, and kinship life. In social life they help one another, in the economy they lend one another to the means of production and consumption, that is location and fishing gear, in their kinship,Â they regar on one blood so that they care about one another, including in educating neighboring children and providing treatment to their sick neighbors and in religion interlocking each other and remindingeach others for good things. The religious life of the residents of Soppeisland Hamlet are always praying in congregation, taking part in majelistaklim activities for the ladies as a place for them to improve their religious knowledge and to establish communication with other fellow citizens, carrying outÂ barazanji and carrying out mabaca-bacatradition as a form of expression of feelings gratitude to God Almighty by eating together, sharing food with neighbors and for establishing friendship with others.Keywords: Social life, religion, harmony, Bugis peoplethey regar on one blood so that they care about one another, including in educating neighboring children and providing treatment to their sick neighbors and in religion interlocking each other and remindingeach others for good things. The religious life of the residents of Soppeisland Hamlet are always praying in congregation, taking part in majelistaklim activities for the ladies as a place for them to improve their religious knowledge and to establish communication with other fellow citizens, carrying outÂ barazanji and carrying out mabaca-bacatradition as a form of expression of feelings gratitude to God Almighty by eating together, sharing food with neighbors and for establishing friendship with others.Keywords: Social life, religion, harmony, Bugis people